Kajian Etnobotani Borassus flabellifer Bahan Baku Songkok Recca Ciri Khas Masyarakat Bugis Bone - Nurlaeliana; Satriani; Bachtiar, Tauhidah; H, Anita; Ekawati, Mutmainna; Wahyudi, Fandi; Hasmatang (Jurnal Biogenerasi, 2025)
Borassus flabellifer, commonly known as the lontar palm, is a member of the Arecaceae family that thrives in arid regions and serves as the primary raw material in the production of songkok recca, a traditional handwoven cap. The local community in Pacing Village, Awangpone Subdistrict, Bone Regency, possesses indigenous ethnobotanical knowledge related to the utilization and management of this plant, particularly in the crafting of songkok recca. This study aims to examine the ethnobotanical role of Borassus flabellifer in the traditional songkok recca production process and to explore sustainable practices for its continued use from both ecological and cultural perspectives. Employing a descriptive-exploratory research design, data collection was conducted through surveys and semi-structured interviews using the Participatory Ethnobotany Appraisal (PEA) method. The data were analyzed using qualitative and quantitative descriptive techniques. Findings indicate that Borassus flabellifer holds significant cultural and economic value within the local community. The preparation of raw materials involves harvesting the leaf sheaths, followed by a sequence of traditional processing steps—pounding (cacca-racca), burning, peeling, soaking, and fine-shaving using a traditional tool called paddari—to produce thin, smooth fibers known as racca, which are then used in weaving songkok recca.